A case of severe ketoacidosis as the first clinical manifestation of type 2 diabetes mellitus in a youngster - Bruno Bombaci; Fortunato Lombardo; Stefano Passanisi; Sara Aramnejad; Rossella Morello; Mariella Valenzise; Giuseppina Salzano; Malgorzata Gabriela Wasniewska (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche)
Type 2 diabetes (T2D) is a chronic condition caused by insulin resistance and relative insulin deficiency, leading to disrupted glucose homeostasis. Several genetic, behavioral, and socio-economic factors have been recognized as predisposing factors. The incidence of T2D in the pediatric population is increasing, paralleling the rise in obesity rates among youths. Early diagnosis and initiation of therapy are crucial to preventing or delaying long-term complications. We present the case of a 13-year-old Caucasian boy who presented with respiratory distress and altered consciousness, preceded by fever, cough, polyuria, and polydipsia. Blood gas analysis revealed metabolic acidosis (pH 7.1, Na 129.4 mmol/l, K 3.81 mmol/l, HCO3- 3.4 mmol/l, BE -23.65 mmol/l), ketonemia (4.8 mmol/l), and hyperglycemia (541 mg/dl), consistent with diabetic ketoacidosis. Further investigations, prompted by persistent respiratory distress and increased inflammatory markers, led to the diagnosis of complicated pneumonia. Based on clinical signs of insulin resistance (such as acanthosis nigricans), obesity (BMI 25.6 kg/m2), family history of T2D (father), and after excluding type 1 diabetes, monogenic, and other forms of diabetes, a diagnosis of T2D was eventually established. Following resolution of diabetic ketoacidosis, therapy with metformin was started, with prompt achievement of satisfactory glucose control. This case underscores the possible association between infections, accelerated metabolic decompensation, and severe diabetic ketoacidosis in individuals predisposed to T2D.